Needs Analysis in the Problem Based Learning (PBL) Model Tools and Problems Regarding 7th Grade Students’ Science Learning Outcome at SMPN 2 Bongan - Zulfaidhah Zulfaidhah; Evie Palenewen; A Hardoko (BIODIK, 2018)
This study aims to: analyze the needs of teachers, feasibility and effectiveness in the development of learning tools based on Problem Based Learning (PBL) model to improve 7th grade students' Science learning outcomes in SMPN 2 Bongan. The results of the observation is in the form of teacher needs analysis instrument analyzed using qualitative descriptive. Observation results obtained that the use of Problem Based Learning model in Science learning process had not been optimally implemented in schools, problems obtained in teachers are: 1) teachers still had difficulties in understanding and composing learning tools, 2) teachers still had difficulties in determining the appropriate learning model, 3) teachers were still less creative, 4) lack of facilities and infrastructure provided in schools for teachers to be more innovative in learning. Problems obtained in students are: 1) low mastery on the subject matter, students were only able to answer the problem of C1 to C3 thinking levels, 2) Science learning only embraced the concept so that students felt lack of interest in learning, 3) students were not engaging in learning, 4) low level of student learning outcomes.